Valuation Of Multiple Hyro Reservoir Storage Systems In Competitive Electricity Markets - Bastian Felix (University of Duisburg-Essen, Chair for Management Science and Energy Economics, 2014)
Increasing renewable generation results in growing supply uncertainty. By now hydrostorages are the most efficient way of smoothing uncertain power supply. In liberalized and competitive markets the valuation of hydro storages investment projects needs to take the market information and therefore the uncertainty of electricity prices into account in investment valuation. Besides the investment in new pump storage facilities the extension of existing storage sites may be an opportunity. However, the correct valuation of multiple reservoir storage systems within an uncertain market is a valuation problem with high dimensionality. We propose an approach that applies numerically constructed multinomial recombining price trees to reduce the problem dimension. We present results for a representative case study. In doing so, we apply a spot price model which accounts for the price fundamentals as well as for the price stochastic.
Keywords: L94; C61; Q4; 330; hydroelectric valuation; optimal control; dynamic programming